Platelet membrane biomimetic nanoparticle-based targeted delivery system of simvastatin for the treatment of ischemic stroke - Qin Li; Rongyuan Li; Lu Lin; Meiting Gong; Yu Liang; Daming Sui (PLoS ONE, 2026)
Blood–brain barrier (BBB) disruption and excessive neuroinflammation are pivotal drivers of cerebral ischemia-reperfusion injury. Although simvastatin (SV) possesses potent pleiotropic effects in promoting BBB repair and attenuating inflammation, its clinical translation for ischemic stroke is severely hampered by poor BBB penetration, low lesion accumulation, and the need for high systemic doses that increase the risk of off-target toxicity (e.g., myopathy). To address these barriers, herein, we developed a platelet membrane–biomimetic nanoparticle system (pmPLGA@SV) designed to leverage the innate affinity of platelets for injured vasculature for lesion-targeted SV delivery at a lower effective dose. Physicochemical characterization confirmed the successful cloaking of platelet membranes onto SV-loaded PLGA cores. In vitro, pmPLGA@SV demonstrated superior therapeutic versatility: it effectively scavenged reactive oxygen species in oxygen glucose deprivation/reoxygenation-treated PC12 cells and orchestrated microglial repolarization from a pro-inflammatory M1 phenotype toward an anti-inflammatory M2 state in BV2 cells, significantly modulating the secretion of IL-1β and IL-10. In vivo, pmPLGA@SV treatment dramatically reduced the cerebral infarct volume, exhibiting significant superiority over free SV. Furthermore, longitudinal behavioral assessments over 21 days demonstrated that pmPLGA@SV markedly accelerated motor and sensory-motor functional recovery, accompanied by consistent body weight regain and improved neurological scores. Mechanistically, pmPLGA@SV facilitates a synergistic therapeutic approach by mitigating neuronal oxidative stress and remodeling the inflammatory microenvironment. This study demonstrates that pmPLGA@SV serves as a robust biomimetic platform for the integrated treatment of neurovascular unit damage, offering a promising strategy for long-term neuroprotection and functional rehabilitation following ischemic stroke.